2021
DOI: 10.1159/000517508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <b><i>Bryophyllum pinnatum</i></b> Administration on Wistar Rat Pregnancy: Biochemical and Histological Aspects

Abstract: <b><i>Introduction:</i></b> <i>Bryophyllum pinnatum</i> is widely used in folk medicine. It has neuropharmacological, anti-inflammatory, immunomodulatory, antidiabetic, hepatoprotective, and nephroprotective effects, among others. It also acts on uterine contractility. It is prescribed by practitioners of anthroposophic medicine for preterm labor, insomnia, and emotional disorders, and has other potential uses in obstetrics. As all drugs currently used in preterm labor have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In an in vivo study, the treatment of mice at supratherapeutic levels did not show any effect on liver enzymes, urea nitrogen, or alkaline phosphatase (Torres- Santos et al, 2003;Hosomi et al, 2022). Also the treatment of pregnant wistar rats with B. pinnatum showed no toxicity at therapeutic levels and merely reduced glucose levels (Hosomi et al, 2022). All clinical studies performed so far showed that treatment with B. pinnatum preparations can be considered as safe and well-tolerated, without severe adverse events and only occasional adverse events that included stomachache, diarrhea, and exanthema (Betschart et al, 2013;Simões-Wüst et al, 2018;Mirzayeva et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vivo study, the treatment of mice at supratherapeutic levels did not show any effect on liver enzymes, urea nitrogen, or alkaline phosphatase (Torres- Santos et al, 2003;Hosomi et al, 2022). Also the treatment of pregnant wistar rats with B. pinnatum showed no toxicity at therapeutic levels and merely reduced glucose levels (Hosomi et al, 2022). All clinical studies performed so far showed that treatment with B. pinnatum preparations can be considered as safe and well-tolerated, without severe adverse events and only occasional adverse events that included stomachache, diarrhea, and exanthema (Betschart et al, 2013;Simões-Wüst et al, 2018;Mirzayeva et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, toxic effects were found in myometrial cell lines only when very high doses of press juice or fractions enriched with bufadienolides and flavonoids were used (Santos et al, 2018;Santos et al, 2019). In an in vivo study, the treatment of mice at supratherapeutic levels did not show any effect on liver enzymes, urea nitrogen, or alkaline phosphatase (Torres- Santos et al, 2003;Hosomi et al, 2022). Also the treatment of pregnant wistar rats with B. pinnatum showed no toxicity at therapeutic levels and merely reduced glucose levels (Hosomi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this practice has also been adopted in perinatal centers in Switzerland [ 6 , 111 , 112 , 113 ], which is important, because new tocolytic agents without side effects are strongly needed. For this reason, we can observe significant advances in preclinical and clinical studies of K. pinnata extract regarding its tocolytic effect [ 35 , 114 , 115 , 116 ]. In vitro studies have shown that flavonoids and especially bufadienolides are implicated in the tocolytic effect of K. pinnata , as mentioned in Section 2.1 [ 34 , 35 ].…”
Section: Why Choose Kalanchoe ? Singular Aspects O...mentioning
confidence: 99%